Diphtheritic angina in the tongue and floor of the mouth: unusual presentation. Issue 3 (April 2020) - Solano, N.; Gutiérrez, V.; Ramos, S.; Peraza, A.; Castrillo, A.
Abstract: Diphtheria is an infectious disease caused by Corynebacterium diphtheriae, and is generally characterised by proliferation of the bacteria in the upper respiratory tract, formation of a pseudomembrane, and systemic diffusion of the diphtheria toxin throughout the body. We present the case of a young man with pseudomembranous plaques on the tongue and floor of the mouth, who received systemic and locoregional medical treatment, with a satisfactory outcome after 14 days.